Mechanisms of democratic authoritarianism: de-centring the executive in South Asia and beyond. Issue 8 (17th November 2022) - Bajpai, Rochana; Kureshi, Yasser
ABSTRACT: How do we theorize the unexpected global trend of democratic regression? Building upon recent literature on backsliding, we offer a new conceptualization of the notion of democratic authoritarianism, denoting the use of democratic-looking institutions for the expansion of authoritarian forms of power across different regime types, democratic and authoritarian. Whereas existing accounts of autocratization focus overwhelmingly on the executive, we outline democratic authoritarianism as a broader process involving mechanisms of institutional and ideational capture, which may be initiated and implemented by executives, legislatures, judiciaries as well as non-state organizations, often acting in tandem. Our notion of democratic authoritarianism can explain autocratization in states with both strong and weak elected executives; it recognizes the role of anti-pluralist ideologies and civil society organizations in enabling autocratization. We illustrate our argument through a comparative analysis of contemporary South Asia, which we argue illustrates different variants of democratic authoritarianism. Through detailed case studies of India and Pakistan since 2014, we show that South Asia is significant for understandings of autocratization, notably, the range of instruments deployed and the different stages of democratic authoritarianism, the interplay between state and societal institutions, and the limits of commonly suggested remedies, notably empowering the judiciary and civil society.